2016
DOI: 10.1155/2016/3717650
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an Interactive Value-Adding Data-Driven Model of Consumer Electronics Supply Chain Based on Least Squares Support Vector Machine

Abstract: The differences in supply chains and their competitiveness depend on the differences in supply chain value creation systems. On the basis of the theory of value cocreation, this study investigates the interactive value creation of consumer electronics supply chains from the perspective of the interaction and added value created by the main value creation bodies in supply chains. Least squares support vector machine (LS-SVM) is innovatively introduced into the study on consumer electronics supply chains. A data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nourikhah and Akbari (2016) used Bayesian data analysis with a generalized linear model (GLM) to estimate the overall satisfaction of the users in the form of the posterior distribution of opinions [48]. Wan et al (2016) introduced least squares support vector machine (LS-SVM) innovatively into the study on consumer electronics supply chains [23]. These studies took consumers as a whole, then from the perspective of the supply chain or enterprises, analyzing consumers' interaction impact on supply chain or their features.…”
Section: Research Methods Of Consumer Online Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nourikhah and Akbari (2016) used Bayesian data analysis with a generalized linear model (GLM) to estimate the overall satisfaction of the users in the form of the posterior distribution of opinions [48]. Wan et al (2016) introduced least squares support vector machine (LS-SVM) innovatively into the study on consumer electronics supply chains [23]. These studies took consumers as a whole, then from the perspective of the supply chain or enterprises, analyzing consumers' interaction impact on supply chain or their features.…”
Section: Research Methods Of Consumer Online Communitymentioning
confidence: 99%
“…Nevertheless, with the rapid network development, the "Internet +" technologies that combine information technologies arouse the significant impacts of consumers on the market [22,23]. More and more consumers are active 2 Complexity in expressing their experiences of some bought products or giving purchase suggestions to others [24,25] in the consumer community formed by different media, including cell phone, PC, or PAD [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hsu developed an integrated conceptual model and explored the effects of brand-evangelism-related behavioural decisions of enterprises on VC members [20]. Wan et al used a least squares support vector machine to study consumer electronics supply chains [21]. However, all of the above studies were mainly analyses of the influencing factors but did not consider the differences among VCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, [2] argues that there have been few large scale comparison studies of machine learning models for regression or time series aimed at forecasting problems. For the electronics manufacturing industry, [30] introduced SVM regression to the supply chain of various producers. They concluded that it yields good results compared to other forecasting methods.…”
Section: Literature Reviewmentioning
confidence: 99%